Visualization and simulation of ZnO microstructure with various crystal structures and doping compositions based on XRD patterns using VESTA - Aminnurdin, Dikri; Rini, Ari Sulistyo (Indonesian Physics Communication, 2025)
Crystal structure visualization and X-ray diffraction pattern simulation of various types of ZnO microstructures have been successfully carried out using the VESTA software program. The purpose of this study was to obtain the relationship between the shape of the structure, microstructure, and composition to changes in the pattern and peak diffraction. The software program produces information on the shape of the crystal structure and representative X-ray diffraction patterns for ZnO microstructures. This program requires input in the form of coordinates of each constituent atom, lattice parameters, and spatial symmetry. The output obtained is a graph of the diffraction pattern and crystal structure that provides an overview of the profile and type (phase) of the ZnO microstructure. The results showed that the peak position and intensity of the diffraction pattern were influenced by the arrangement of atoms in the unit cell. In variations in structure and microstructure, the position of the diffraction peak provides a different picture for each type of structure depending on the arrangement of atoms in the unit cell, where each crystal structure has a different position and spatial symmetry, resulting in different diffraction patterns. The nanorod structure has a monoclinic crystal system (a ≠ b ≠ c) with a space group of C 2 / c and lattice parameters a = 15.4170 Å, b = 25.3560 Å, and c = 14.3840 Å. The nanowire structure has a triclinic crystal system (a ≠ b ≠ c) with lattice parameters a = 12.0380 Å, b = 2.4910 Å, c = 16.8890 Å and a space group of P-1 and is the simplest form of symmetric lattice. The nanoflower structure has an orthorhombic crystal system (a ≠ b ≠ c) with lattice parameters a = 9.47310 Å, b = 13.52960 Å, c = 29.0220 Å and space group P b c a.